(untitled) (Texas Journal of Agriculture and Biological Sciences, 2026)
This article analyzes the assessment of the meliorative condition of irrigated lands using modern devices. Modern technologies were applied to study the level of soil salinity, its changing trends, and the effectiveness of meliorative measures. The article also develops scientifically grounded recommendations for effective reclamation measures to combat soil salinization